Childcare Professionals: A Practical Career Guide - Hamilton, Tracy Brown (Rowman & Littlefield Publishers, 2022)
Welcome to the childcare field! If you are interested in a career as a childcare professionals, you’ve come to the right book. What exactly do these people do on the job every day? What kind of skills and educational background do you need to succeed in this field? How much can you expect to make, and what are the pros and cons of these various professions? Is this the right career path for you? How do you avoid burnout and deal with stress? This book can help you answer these questions and more. Chidcare Professionals: A Practical Career Guide, which includes interviews with professionals in this field which has proven to be a stable, lucrative, and growing profession. •Day care provider •Day care owner •Nanny •Preschool teacher •Teaching assistant